Investigation of Wavelength Division Multiplexing Technique - Alwan, Mohammed Talfan; Mohammed, Omar Ali; Ahmed, Muafaq Khawam; Abdulwahid, Mayada Mohammed; Fathi, Mohannad Mohsen (American Journal of Botany and Bioengineering, 2025)
This investigation explores the principles, components, and applications of Wavelength Division Multiplexing (WDM) technology. WDM enables the simultaneous transmission of multiple optical signals over a single fiber, allowing for significant increases in network capacity and infrastructure utilization . Providing a comprehensive overview of WDM systems, this study covers fundamental concepts, operational techniques, network architectures, and the advantages they offer within modern communication networks. The analysis proceeds to consider the challenges associated with WDM deployment and identifies emerging trends that point to future developments in the field. Finally, representative applications demonstrate the practical utility of WDM technology.